Compensatory conservation measures for an endangered caribou population under climate change. Issue 1 (December 2018) - Bauduin, Sarah; McIntire, Eliot; St-Laurent, Martin-Hugues; Cumming, Steven
Abstract Future human land use and climate change may disrupt movement behaviors of terrestrial animals, thereby altering the ability of individuals to move across a landscape. Some of the expected changes result from processes whose effects will be difficult to alter, such as global climate change. We present a novel framework in which we use models to (1) identify the ecological changes from these difficult-to-alter processes, as well as (2) the potential conservation measures that are best able to compensate for these changes. We illustrated this framework with the case of an endangered caribou population in Québec, Canada. We coupled a spatially explicit individual-based movement model with a range of landscape scenarios to assess the impacts of varying degrees of climate change, and the ability of conservation actions to compensate for such impacts on caribou movement behaviors. We found that (1) climate change impacts reduced movement potential, and that (2) the complete restoration of secondary roads inside protected areas was able to fully offset this reduction, suggesting that road restoration would be an effective compensatory conservation action. By evaluating conservation actions via landscape use simulated by an individual-based model, we were able to identify compensatory conservation options for an endangered species facing climate change.